Genome-Wide Transcriptional Profile Analysis of Prunus persica in Response to Low Sink Demand after Fruit Removal - Duan, Wei; Xu, Hongguo; Liu, Guotian; Fan, Peige; Liang, Zhenchang; Li, Shaohua (Frontiers in Plant Science, 2016)
Prunus persica fruits were removed from one-year-old shoots to analysis photosynthesis, chlorophyll fluorescence and genes changes in leaves to low sink demand caused by fruit removal (–fruit) during the final stage of rapid fruit growth. A decline in net photosynthesis rate was observed, accompanied with a decrease in stomatal conductance. The intercellular CO2 concentrations and leaf temperature increased as compared with control (remaining fruits on the shoot, +fruit). Moreover, low sink demand significantly inhibited the donor side and the reaction center of photosystem II. 382 genes in leaf with an absolute value of log2 ratio≥1 change in expression level, representing 116 up- and 266 down-regulated genes except for unknown transcripts. Among these, 25 genes for photosynthesis were down-regulated, 69 stress and 19 redox genes up-regulated under the low sink demand. These studies revealed high leaf temperature may result in a decline of net photosynthesis rate through decreased in genes related to photosynthesis and increased redox and stress genes, especially heat shock proteins genes. The complex changes in genes at the transcriptional level under low sink demand and provided useful starting points for in-depth analyses of source-sink relationship in P. persica.